The Effect of Academic Culture and Collaborative Culture as Collaborative Academic Culture to Improve The Innovative Behavior in Universities - Sihite, Otto Berna; Sinaga, Poltak; Hidayat, Dylmoon; Sijabat, Rosdiana (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Leaders in various universities design and participate in education by constructing and developing fresh and new ideas and innovations to create efficient teaching methods across all departments. Additionally, millennials are the technology-literate generation, making this an exciting time for them as they try to meet market demand. This fact will serve as the foundation for determining whether the university's collaborative and academic culture impacts the lecturers' innovative behavior. The 101 samples of lecturers were taken from 5 universities in the Jakarta and Java area. The Structural Equation Model (SEM) of Smart PLS was used in this analysis. The results indicated whether Collaborative Culture and Academic Culture affect Innovative Behavior. From the results of this analysis, it is essential to develop and improve future methods of combining collaborative and academic culture to create a Collaborative Academic Culture. This method would in turn improve innovation in the university, as the country had set a goal to increase the collaboration between higher education stakeholders in society. It is also expected that the derivation of the two variables will further develop the effectiveness of quality teaching in higher education. Keywords: collaborative culture, academic culture, innovative behavior